SARS-CoV-2 Related Morbidity and Mortality in Patients Undergoing Hemodialysis at The Kirkuk Hemodialysis Center - Fadhil muhaldeen; Abdullah Raoof (Kirkuk Journal of Medical Sciences)
Background: Coronavirus disease 2019 (COVID-19) is a new emerging disease caused by SARS-CoV-2, first discovered in Wuhan, China, in December 2019. Infected patients of all age groups with associated medical diseases such as chronic kidney disease (CKD) stage five -end stage renal disease (ESRD) on hemodialysis are likely to have a higher risk of developing severe COVID-19 compared to patients without disease. The study aimed to address morbidity and mortality related to SARS-CoV2 infection in hemodialysis patients at the Kirkuk dialysis centre.Methods: A prospective observational study that enrolled 385 COVID-19 patients with CKD-stage 5 (ESRD), who were on a regular hemodialysis program in the dialysis center in Kirkuk city for a period of 6 months.Results: In hemodialysis patients, the incidence of SARS-CoV2 infection was 80 (20.75%), among these 80 patients, 43(53.75%) required hospital admission due to the severity of the disease, 32 (40%) were admitted to the intensive care unit and received ventilation, 19 patients (23.75%) died from complications related to SARS-CoV-2.Conclusion: There is a significant incidence of hospital admission and the need for ventilation among patients, as well as a notable mortality rate was observed in COVID-19 patients undergoing hemodialysis, with specific risk factors such as bronchial asthma, the presence of AV fistula, and type 2 diabetes mellitus contributing to a higher mortality percentage.